Dietary intake, body composition, and nutritional knowledge of elite handball players - Arnaoutis, G.; Alepoudea, M.; Tambalis, K. D.; Sidossis, L. S. (Nutrients, 2024)
Nutrition affects both body composition and, consequently, athletic performance. Only a few studies have assessed the nutritional behavior and knowledge of elite players. The present study aimed to assess the dietary intake, body composition, and nutritional knowledge of elite handball players. Thirty-nine handball players (age: 23.2 ± 2.7 years, weight: 88.2 ± 10.1 kg, height: 1.87 ± 0.07 m, and years of training: 13 ± 2) participated in the study. The athletes completed a set of anthropometric measurements, a 24 h food recall, and a translated edition of Abridged Nutrition for Sport Knowledge Questionnaire (A-NSKQ). The average body fat percentage was 16.7 ± 3.8%, while the average fat free mass was 73.9 ± 8.5 kg. The athletes` average daily energy intake was 2606.6 ± 756 kcal, while the average daily intake for carbohydrates, proteins, and fats was 243.85 ± 107.79 g [2.8 ± 1.3 g/kg BW/d—37.2 ± 10.5% of Total Energy Intake (TEI)], 131.59 ± 53.28 g (1.51 ± 0.7 g/kg BW/d—20.3 ± 6.9% of TEI), and 117.65 ± 40.52 g (40.9 ± 9.9% of TEI), respectively. For iron, calcium, and vitamin D, the average daily intakes were 19.33 ± 10.22 mg, 1287.7 ± 676.42 mg, and 3.22 ± 3.57 mcg respectively. The average success rate on the A-NSKQ was only 38.5 ± 10.7% out of 100. Elite handball players exhibit inadequate dietary intake and sports nutrition knowledge. Nutritional education should be a primary concern towards the amelioration of their athletic performance.